2014
DOI: 10.1080/10888705.2013.856767
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Automated Scatter Feeders on Captive Grizzly Bear Activity Budgets

Abstract: Although captive bears are popular zoo attractions, they are known to exhibit high levels of repetitive behaviors (RBs). These behaviors have also made them particularly popular subjects for welfare research. To date, most research on ursid welfare has focused on various feeding methods that seek to increase time spent searching for, extracting, or consuming food. Prior research indicates an average of a 50% reduction in RBs when attempts are successful and, roughly, a 50% success rate across studies. This res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Although, as noted above, mate-seeking behavior may be causally related to the May through July occurrence of stereotypies, the times at which these stereotypies occurred still appeared entrained to the feeding schedules. Past research has shown similar patterns for stereotypic pacing in zoo bears, with pacing occurring in anticipation of food events and reduced as a result of providing multiple feeding opportunities [26,37,[59][60][61].…”
Section: Daily Activitymentioning
confidence: 79%
“…Although, as noted above, mate-seeking behavior may be causally related to the May through July occurrence of stereotypies, the times at which these stereotypies occurred still appeared entrained to the feeding schedules. Past research has shown similar patterns for stereotypic pacing in zoo bears, with pacing occurring in anticipation of food events and reduced as a result of providing multiple feeding opportunities [26,37,[59][60][61].…”
Section: Daily Activitymentioning
confidence: 79%
“…Increased activity levels are often associated with improved captive welfare, but not if the activity stems from stereotypic behaviours (Bashaw et al, 2003;Andrews and Ha, 2014); using dead-reckoned tracks we could investigate this in unprecedented detail (see below). Both individuals collared in London Zoo showed higher daily VeDBA values when a partial pony carcass had been fed compared to rabbits but days where esh chunks had been fed showed greatest variability in VeDBA (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear why this was the case, although other researchers have used "noncontingent reinforcement" (NCR) procedures to decrease aberrant (undesired) responses and increase desired behaviors (for reviews, see [38,39]). Similarly, response-independent schedules have been successful at reducing stereotypic activity and increasing naturalistic foraging responses in zoo animals [40,41].…”
Section: Response-independent Schedules and Approach/contact Behaviormentioning
confidence: 99%